Systematic Literature Review: Principal’s Leadership in Improving Teachers’ Performance - Maryani, Desi (PPSDP International Journal of Education, 2025)
This study aims to systematically investigate the influence of principal leadership on teacher performance through a Systematic Literature Review (SLR) approach. A total of fifteen peer-reviewed journal articles published between 2020 and 2024 in Indonesia were analyzed to identify patterns, findings, and research gaps related to this topic. The results indicate that leadership styles particularly transformational, democratic, and control based positively affect teacher performance, although the magnitude of influence varies depending on contextual and mediating factors such as work motivation, organizational culture, and infrastructure management. The novelty of this review lies in mapping the interplay between leadership styles and school-specific contextual variables, a dimension underexplored in previous studies. This study contributes to educational leadership literature by providing evidence-based recommendations for developing adaptive leadership models tailored to school characteristics. It also highlights the need for further qualitative exploration to understand the emotional and relational dynamics between school leaders and teachers in diverse educational settings.